An International Investigation of the Prevalence of Negative Visitor Behaviour in the Zoo - Courtney Collins; Yotam Barr; Sean McKeown; Juan Scheun; Claudia Tay; Ruth O’Riordan (Animals, 2023)
Negative visitor behaviour is an understudied area of zoo research, even though negative actions can have serious implications for animal welfare. This research project investigated the prevalence of negative visitor behaviours at four different zoos. It included observations of visitors at seven different taxa exhibits and three different types of enclosures. A modified version of behaviour sampling was used to record visitor behaviour and the activity of the animals, while a negative binomial regression was conducted to test the significance of several predictor variables against the number of negative behaviours observed. Negative visitor behaviour was relatively common, occurring in 57% of observations. Banging was the most commonly observed negative action. Negative behaviours were influenced by zoo (p < 0.001), species (p < 0.001) and the number of visitors present (p < 0.001). The charismatic species were the most harassed animals included in the study, while children were the most likely to engage in negative behaviour. Negative visitor behaviours occurred more frequently when animals were active and in close proximity to visitors. It is imperative for zoos to understand visitors’ behaviour so that they can effectively communicate with their visitors to minimise negative actions and promote better animal welfare.